Introducing Hydrogeology. - Robins, Nicholas (Dunedin Academic Press, 2020)
A concise introduction to hydrogeology, the branch of earth science that deals with the chemical, physical, and biological interactions between rock, soil, water, nature and society. Copiously illustrated in colour and drawing on international examples, it is an ideal starting text for students and those whose work raises issues of groundwater.